2011
DOI: 10.1097/iae.0b013e31820f49ea
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Iatrogenic Peripheral Retinal Breaks in 23-Gauge Vitrectomy for Macular Diseases

Abstract: The incidence of iatrogenic peripheral retinal breaks during vitrectomy for macular diseases is significantly lower in 23-gauge vitrectomy than in 20-gauge vitrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 28 publications
3
19
1
2
Order By: Relevance
“…The findings of Nakano T et al (2011) support those of Issa SA et al They reported an incidence of 1.1% in 23 G group versus 8.5% in 20 G group, in cases undergoing vitrectomy for macular diseases. Rizzo S (2010) found no statistical difference in the incidence of RD, 1.7% after sutureless vitrectomy and 1.2% after conventional 20-gauge vitrectomy.…”
Section: Khanduja S Et Al Minimally Invasive Vitrectomy Surgery Insupporting
confidence: 86%
“…The findings of Nakano T et al (2011) support those of Issa SA et al They reported an incidence of 1.1% in 23 G group versus 8.5% in 20 G group, in cases undergoing vitrectomy for macular diseases. Rizzo S (2010) found no statistical difference in the incidence of RD, 1.7% after sutureless vitrectomy and 1.2% after conventional 20-gauge vitrectomy.…”
Section: Khanduja S Et Al Minimally Invasive Vitrectomy Surgery Insupporting
confidence: 86%
“…Similar to our study, other authors have also found a protective effect of microcannulas, especially when posterior vitreous detachment was induced during surgery [3,4,5,7]. However, in contrast to these other authors, we did not find any influence of the diagnosis on the rate of intraoperative retinal break formation [5,7]. …”
Section: Discussioncontrasting
confidence: 55%
“…The issue of compromised wound integrity due to the lack of sutures possibly leading to complications such as hypotony, endophthalmitis and choroidal hemorrhage has been a matter of discussion [1]. However, one other important difference between the sutureless and the conventional techniques are the microcannula-guided entry sites into the eye [2,3,4,5,6,7]. Even though vitreous incarceration to the microcannulas has been documented, the microcannula system has been proposed to lower the risk of retinal dragging (with formation of iatrogenic retinal defects) during vitrectomy [3,4,5,7].…”
Section: Introductionmentioning
confidence: 99%
“…10,[22][23][24][25][26][27][28][29][30][31][32] After NVS, Saito et al 5 reported no retinal breaks during the follow-up period. In our study, similar incidence of retinal breaks in two groups suggests that NVS does not negatively affect the retina.…”
Section: Discussionmentioning
confidence: 99%